Optimization of BUMDes in the Social Development of Ponggok Village Community, Polanharjo, Klaten - Hidayah, Sri Noor Mustaqimatul (Community Development: Jurnal Pengembangan Masyarakat Islam, 2023)
Optimization of BUMDes in the Social Development of Ponggok Village Community, Polanharjo, Klaten. This study aims to reveal the Optimization of BUMDes in the Social Development of Ponggok Village Community, Polanharjo, Klaten. Research on Optimizing BUMDes in Village Community Social Development was conducted using a qualitative approach with the type of field research with data collection techniques using Interview, Observation and Documentation techniques. The research subjects or informants in this study were the head of Ponggok Village, the Director of BUMDes Tirta Mandiri and the Ponggok Village Community. The results showed that the optimization of the Tirta Mandiri BUMDes in Ponggok Village in social development was implemented in various programs, namely: Community participation in every BUMDes program, Social Activities (compensation), one bachelor's house program, increasing the productivity of BUMDes human resources with training and capacity building of human resources. , Development of health services, Development of community productive activities through SMEs, and routine village recitations. Optimization of BUMDes Tirta Mandiri Ponggok Village in social development aims to improve the quality of human life in a complete way, namely meeting human needs ranging from physical to social needs.